Acute acalculous cholecystitis by Epstein-Barr virus infection: a rare association - Liliana Branco; Maria Vieira; Cristiana Couto; Maria D. Coelho; Carla Laranjeira (MDPI AG, 2015)
Acute acalculous cholecystitis (AAC) is a rare complication of Epstein Barr virus (EBV) infection, with only a few cases reported among pediatric population. This clinical condition is frequently associated with a favorable outcome and, usually, a surgical intervention is not required. We report a 16-year-old girl who presented with AAC following primary EBV infection. The diagnosis of AAC was documented by clinical and ultrasonographic examination, whereas EBV infection was confirmed serologically. A conservative treatment was performed, with a careful monitoring and serial ultrasonographic examinations, which led to the clinical improvement of the patient. Pediatricians should be aware of the possible association between EBV and AAC, in order to offer the patients an appropriate management strategy.